Hubungan antara skor hasil bacaan heat detector dengan gambaran sitologi vagina sebagai parameter penentuan estrus pada kambing - Meydilasari, Nanda Irsa; Hernawati, Tatik; Lestari, Tita Damayanti; Safitri, Erma; Sardjito, Trilas; Ismudiono, Ismudiono; Hidanah, Sri (Universitas Airlangga, 2020)
This study aimed to determine the relationship between heat detector reading results and the feature of vaginal swab preparations as a parameter for determining estrus in Peranakan Etawa goats. Five healthy non-pregnant goats weighing 20-30 kg, were synchronized using PGF2α (7.5 mg Dinoprost, Enzaprost) intramuscularly twice with 11 days interval. Vaginal cytology examination began the day after the second PGF2α injection. The heat detector (Draminski®, DramiÅ„ski SA, Poland) is an estrus detecting device based on the amount of electric current flowing through the vaginal mucus. Spearman correlation analysis showed a relationship (p <0.05) between heat detector reading and estrus detection based on vaginal cytology. The heat detector readings were very significantly correlated positively (p <0.01) with the number of epithelial cells (coefficient correlation, r= 0.564), but negatively correlated with the number of cornified cells (r = –0.854), and also significantly correlated positively (p <0.05) to the number of leukocytes (r = 0.487). The estrus stages were significantly correlated positively (p <0.05) only to the number of leukocytes (r = 0.918). Likewise, the number of epithelial cells was highly correlated negatively (p <0.01) only to cornified cells (r = –0,643), and the number of cornified cells was significantly correlated negatively (p <0.05) only to the number of leukocytes (r = –0.472). It could be concluded that the features of the proestrus, estrus and metestrus stages based on the goat vaginal cytology was correlated with the reading results of the heat detector.